Trudne pytania o los Ojczyzny. Konstrukcje pytające na transparentach z ukraińskich protestów ulicznych w lipcu 2025 roku - Tułacz, Alan (Studia Ukrainica Posnaniensia, 2025)
Questions often accompany people when the need to understand life, the surrounding world or a particular situation arises. The controversial bill No. 12414, adopted by the Verkhovna Rada of Ukraine in July 2025 and de facto marginalizing the role of anti-corruption bodies in Ukraine, sparked a series of protests and created new protest slogans, among which interrogative structures played a significant role. This paper attempts to analyze the slogans displayed on banners during street protests against the controversial bill in light of political discourse and protest linguistics. The study demonstrates that the most numerous groups of interrogative structures are rhetorical and emotional interrogative structures, imbuing the entire political discourse in contemporary Ukraine with a specific emotional charge.